An empirical model for the polarization of pulsar radio emission - Melrose, D; Miller, A; Karastergiou, A; Luo, Q (2006)
We present an empirical model for single pulses of radio emission from pulsars based on Gaussian probability distributions for relevant variables. The radiation at a specific pulse phase is represented as the superposition of radiation in two (approximately) orthogonally polarized modes (OPMs) from one or more subsources in the emission region of the pulsar. For each subsource, the polarization states are drawn randomly from statistical distributions, with the mean and the variance on the Poincaré sphere as free parameters. The intensity of one OPM is chosen from a lognormal distribution, and the intensity of the other OPM is assumed to be partially correlated, with the degree of correlation also chosen from a Gaussian distribution. The model is used to construct simulated data described in the same format as real data: distributions of the polarization of pulses on the Poincaré sphere and histograms of the intensity and other parameters. We concentrate on the interpretation of data for specific phases of PSR B0329+54 for which the OPMs are not orthogonal, with one well defined and the other spread out around an annulus on the Poincaré sphere at some phases. The results support the assumption that the radiation emerges in two OPMs with closely correlated intensities, and that in a statistical fraction of pulses one OPM is invisible. © 2005 RAS.